Intervensi Massage Aromaterapi (Lavender) terhadap Penurunan Intensitas Nyeri Penderita Neuropathy Diabetic - Rizzi Triputri Maya Meutia; Jenny Marlindawani; Kiking Ritarwan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze lavender aromatherapy massage intervention to reduce pain intensity in DN patients. The method used is quantitative research with a Quasy Experimental Non-Equivalent Control Group Pretest-Postest Design. The results of this study indicate a difference between the mean value of pain intensity in the intervention group and the control group after being given treatment with the obtained value (t = -5.155, p-value = 0.000). This study concludes that lavender aromatherapy massage has a significant effect on reducing pain intensity in patients with diabetic neuropathy.